Addressing the challenges of phenotyping pediatric pulmonary vascular disease. (January 2017) - Goss, Kara N.; Everett, Allen D.; Mourani, Peter M.; Baker, Christopher D.; Abman, Steven H.
Pediatric pulmonary vascular disease (PVD) and pulmonary hypertension (PH) represent phenotypically and pathophysiologically diverse disease categories, contributing substantial morbidity and mortality to a complex array of pediatric conditions. Here, we review the multifactorial nature of pediatric PVD, with an emphasis on improved recognition, phenotyping, and endotyping strategies for pediatric PH. Novel tailored approaches to diagnosis and treatment in pediatric PVD, as well as the implications for long-term outcomes, are highlighted.